How Electronic Word of Mouth, Customer Experience, and Satisfaction Shape Consumer Purchase Decisions in Specialty Food Retail Tukies Coconut Shop? - Putu Ayu Titha Paramita Pika; Ni Putu Dian Puspita; Ida Ayu Oka Martini (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyze the effect of Electronic Word of Mouth (E-WOM), customer experience, and customer satisfaction on purchase decisions at Tukies Coconut Shop in Bali. This research employs a quantitative approach using a survey method. The population consists of people in Bali who are aware of Tukies Coconut Shop through direct visits or social media exposure. A purposive sampling technique was applied, resulting in 156 respondents. Data were collected through questionnaires using a five-point Likert scale and analyzed using multiple linear regression with SPSS software. The results indicate that Electronic Word of Mouth has a positive and significant effect on purchase decisions, customer experience has a positive and significant effect on purchase decisions, and customer satisfaction also has a positive and significant effect on purchase decisions at Tukies Coconut Shop. These findings suggest that positive online information, enhanced customer experiences, and higher levels of customer satisfaction increase consumers’ likelihood of making purchasing decisions. This study provides practical insights for culinary MSMEs in developing effective digital marketing strategies and customer-centered experiences.